MYCELIAL GROWTH OF Monilinia fructicola AND Trichothecium roseum IN SEVERAL TEMPERATURES AND SENSITIVITY OF ANTAGONIST TO FUNGICIDES AND PHOSPHITES - MOREIRA, Luciene Martins; MAY DE MIO, Louise Larissa (Scientia Agraria, 2007)
Brown rot is an important disease economically in peachtree cultivation and is mainly controlled by fungicides but biological control has been proposed as an alternative. Thus the present study aimed to investigate the growth of Monilinia fructicola and Trichothecium roseum in different temperatures and also establish the effect of fungicides and phosphites on the mycelia growth inhibition of antagonist. The mycelia growth of T. roseum and five M. fructicola isolates was assessed in the BDA culture medium at 5, 10, 15, 20, 25, 30 and 35 °C. The sensitivity of the T. roseum antagonist isolate was defined in culture medium with 1, 10 and 100 mg L-1 of the iprodione, azoxystrobin, captan, mancozebe, tebuconazole, iminoctadine tris albesilate fungicides and Ca and K phosphites. Results showed that the optimum, maximum and minimum temperatures for T. roseum mycelial growth were 20 to 25, 36 and 4,9 oC, respectively and for the pathogen were from 20 to 25, 35 and from 4,9 to 2,5 °C. The study of the effects of the chemical products showed that at the concentration of 100 mg L-1 the phosphites and the captan, azoxystrobin and iminoctadine fungicides exercised less inhibition of the antagonist, suggesting that these products may be used in an integrated control program for brown rot.